The determinants of sovereign risk premiums in the UK and the European government bond market: the impact of Brexit - Samir Kadiric (International Economics and Economic Policy, 2022)
This paper analyzes recent developments in the British and European government bond markets with reference to the UK's decision to leave the European Union. The two main goals of the study are, firstly, to examine whether the Brexit referendum result has affected the risk premium and, secondly, whether there are any changes in risk pricing following the referendum. The paper finds a significant impact of the Brexit referendum on the risk premium in selected economies. Furthermore, the results suggest that there is a considerable change in risk pricing after the announcement of the referendum result. Credit default risk and the risk aversion play a much important role in the post-referendum period than they did prior to the vote, particularly in the UK.
Keywords: E43; E44; F36; G12; G15; 330; Asset pricing; Government bond yield spreads; Risk premium; UK; Europe; Brexit